MICROBIAL EOR STUDY TO IMPROVE SWEEP EFFICIENCY IN CALTEX FIELDS PHASE 1 – NUTRIENT SELECTION - Sri Kadarwati; M. Udiharto; Noegroho Hadi Hs; Joseph P. Brinkman; Bangun Yulianto (Testing Center for Oil and Gas LEMIGAS, 2002)
The objective of this research is to find a cost effective nutrient that will stimulate the growth of in-situ microbes in Caltex Pacific Indonesia (CPI) oil fields to create sufficient biological products to plug high-permeability reservoir thief zones. If successful, injection fluids may be diverted into unswept regions of the reservoir, increasing the sweep efficiency und extending the production life of watered- out oil fields. This paper describes how a wide range of nutrients were researched and tested in the laboratory to achieve the objective. The primary findings of this study show that several primary nutrients were successful at creating bioproducts at high temperature, low salinity, reservoir conditions, and that molasses may be the most cost effective nutrient for all three CPI waterflooded reservoirs tested: Balam South, Bangko, and Minas fields. As a result of this work, laboratory studies were started to see to if the microbial growth created in laboratory test tubes can be recreated within reservoir core plugs to achieve sufficient permeability reduction to justify field trial (s). The core flood process and techniques will be presented in a separate paper.